2005
DOI: 10.1093/rheumatology/keh608
|View full text |Cite
|
Sign up to set email alerts
|

Hand surgery in rheumatoid arthritis: state of the art and suggestions for research

Abstract: Despite recent advances in medical treatment, surgery still plays a role in the clinical management of RA-associated hand dysfunction. However, the majority of the available studies showed methodological flaws that prevented a clear definition of both surgical indications and criteria for choosing any specific procedure. Suggestions for further investigations are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 176 publications
0
18
0
1
Order By: Relevance
“…There are still concerns about the assessment tools and methods used to gather information [10,45] and our inability to compare results universally. Standardization of tools and methods between groups is required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are still concerns about the assessment tools and methods used to gather information [10,45] and our inability to compare results universally. Standardization of tools and methods between groups is required.…”
Section: Resultsmentioning
confidence: 99%
“…This can be difficult to do since the surgical management of rheumatoid hand disease is still not standardized; many different approaches are proposed, each in a relatively small number of published studies. The low quality and heterogeneity of experimental designs has prevented the definition of universally accepted guidelines for clinical practice [10]. Evaluating the outcome of a single surgical intervention, in an individual with a progressive, systemic disease that affects multiple joints, introduces many variables into the evaluation of outcomes, these need to be recognized and addressed by the tools used for its measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in medical therapy have provided greater systemic control of rheumatoid arthritis, but have perpetuated the practice of rheumatologists referring patients to hand surgeons late in the disease process, when operative intervention is more challenging. Regardless, literature has demonstrated that patients with severe ulnar drift deformity benefi t from surgical intervention [ 30 ]. Despite the absence of a consensus on how to surgically approach ulnar drift deformity, a few principles exist.…”
Section: Surgical Management Of Ulnar Drift Deformitymentioning
confidence: 99%
“…Surgical outcomes are generally poorer among patients with RA compared with osteoarthritis, but many patients experience sustained pain relief and can return to many of their usual activities of daily living [ 34 -36 ]. For example, among patients with upper extremity disability, total wrist fusion (TWF) and silicone metacarpophalangeal arthroplasty (SMPA) remain two of the most predictably effective surgical interventions [ 37 ]. An ongoing, prospective multicenter study of RA patients has consistently demonstrated that SMPA enhances self-reported hand function, restores anatomic fi nger position, and improves arc and range of motion, even for severe deformities [ 38 -41 ] (Figs.…”
Section: Surgical Management Of Ramentioning
confidence: 99%